Pengaruh Media Sosial terhadap Perubahan Bahasa Gaul di Kalangan Remaja - Bachtiar; Sumarno (Jurnal Ragam Pengabdian, 2026)
Study aims to analyze the role of social media in changes in slang language use among adolescents and young adults. Social media has become a primary space for interaction, enabling the rapid and widespread diffusion of new vocabulary. This research employed a mixed-methods approach with an explanatory sequential design. Quantitative data were collected through an online questionnaire involving 117 active social media users, while qualitative data were obtained through semi-structured interviews with selected respondents. The findings indicate that social media platforms such as TikTok, Instagram, and WhatsApp play an important role in the emergence and dissemination of slang language. Higher intensity of social media use shows a tendency toward a positive relationship with increased slang usage. Qualitative findings reveal that slang is used as a means of self- expression, social bonding, and group identity formation. However, respondents also reported potential misunderstandings, particularly in communication with older individuals or in formal contexts. Therefore, the use of slang language needs to be adjusted according to communicative contexts to maintain effective and appropriate language use.